ANALISIS FAKTOR-FAKTOR PENYEBAB KREDIT MACET PADA CU. FAOMASI KECAMATAN TELUKDALAM KABUPATEN NIAS SELATAN - Telaumbanua, Anita C. (Balance: Jurnal Riset Akuntansi dan Bisnis, 2022)
This study aims to determine the internal factors that cause bad loans in CU. Faomasi Telukdalam from 2016-2020. The data analysis method used is a descriptive qualitative method. Data collection techniques using observation, interviews, and documentation. The data analysis technique uses an interactive analysis model consisting of a data reduction process, data presentation, and verification or drawing conclusions. The results of this study indicate that internal factors cause bad loans in CU. Faomasi Telukdalam in inaccurate analysis, CU. Faomasi Telukdalam provides credit because it has family relations, and is a CU. Faomasi Telukdalam is lacking in credit supervision. So it can be concluded that the analysis is not appropriate, CU. Faomasi Telukdalam provides credit because it has family relations, and is a CU. Faomasi Teluk Dalam lack of credit supervision is an internal factor causing bad loans in CU. Faomasi Telukdalam from 2016-2020. The suggestions put forward by the researcher are 1) That in conducting an analysis of members who apply for loans, an assessment should be carried out based on the 5C principle and 2) In granting credit to members who apply for credit, it should be done objectively without any interference from related parties because they have family relationships.